Isolation of Antiosteoporotic Compounds from Seeds of Sophora japonica - Abdallah, Hossam M.; Al-Abd, Ahmed M.; Asaad, Gihan F.; Abdel-Naim, Ashraf B.; El-halawany, Ali M. (PLOS ONE, 2014)
Chemical investigation of Sophora japonica seeds resulted in the isolation of seven metabolites identified as: genistin (1), sophoricoside (2), sophorabioside (3), sophoraflavonoloside (4), genistein 7,4’-di-O-β-D-glucopyransoide (5), kaempferol 3-O-α–L-rhamnopyranosyl(1→6)β-D-glucopyranosyl(1→2)β-D-glucopyranoside (6) and rutin (7). Compounds 1, 2 and 5 showed significant estrogenic proliferative effect in MCF-7 cell in sub-cytotoxic concentration range. Compounds 1 and 2 showed minimal cell membrane damaging effect using LDH leakage assay. Accordingly, compound 2 (sophoricoside, (SPH)) was selected for further in-vivo studies as a potential anti-osteoporosis agent. The anti-osteoporotic effect of SPH was assessed in ovarectomized (OVX) rats after oral administration (15 mg/kg and 30 mg/kg) for 45 days compared to estradiol (10 µg/kg) as a positive control. Only in a dose of 30 mg/kg, SPH regained the original mechanical bone hardness compared to normal non-osteoporotic group. However, SPH (15 mg/kg) significantly increased the level of alkaline phosphatase (ALP) to normal level. Treatment with SPH (30 mg/kg) increased the level of ALP to be higher than normal group. SPH (15 mg/kg) did not significantly increase the serum level of osteocalcin (OC) compared to OVX group. On the other hand, treatment with SPH (30 mg/kg) significantly increased the level of OC to 78% higher than normal non-ovarectomized animals group. In addition, SPH (15 mg/kg) decreased the bone resorption marker, acid phosphatase (ACP) to normal level and SPH (30 mg/kg) further diminished the level of serum ACP. Histopathologically, sophoricoside ameliorated the ovarectomy induced osteoporosis in a dose dependent manner. The drug showed thicker bony trabeculae, more osteoid, and more osteoblastic rimming compared to OVX group.